THE INFLUENCE OF PRODUCT RATINGS AND SHOPEE CONSUMER REVIEWS ON WARDAH PRODUCT PURCHASE DECISIONS IN BOGOR REGENCY - Nur Fatihah Rizkia; B. Retno Pratiwi Sakti (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of product ratings and consumer reviews on purchasing decisions for Wardah products on the Shopee e-commerce platform in Bogor Regency . The study used a quantitative approach with an associative research type . The research sample consisted of 100 respondents selected using a purposive sampling technique . Data were collected through a Likert- scale -based questionnaire and analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that partially product ratings have a positive and significant effect on purchasing decisions with a calculated t value of 2.260 and a significance of 0.026. Consumer reviews also have a positive and significant effect with a calculated t value of 6.348 and a significance of 0.000, and have a more dominant influence . Simultaneously , product ratings and consumer reviews have a significant effect on purchasing decisions with a calculated F value of 567.534 and a significance of 0.000. The coefficient of determination (R²) value of 0.921 indicates that both independent variables are able to explain 92.1% of the variation in purchasing decisions . This finding confirms that consumer ratings and reviews are important factors in influencing consumer behavior. consumers in the context of online purchasing .